INFORMATION EXCHANGE PROVISION CREATING VIRTUAL HIGHER EDUCATION INSTITUTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The computerised distance education system created by School o f Business Administration Turiba (Latvia) has been reviewed in this paper, the main aim o f which is to ensure the full possibility of mastering the speciality of business management through the Internet. The system practically provides the student all the necessary methodical and informational support. The structural specifics, organisation of the study process, the design and development strategy of the given distance education system have been reviewed in this paper. The computerised distance education system has been designed specially taking into account the specifics of Latvia.